The role of speckle tracking echocardiography in the identification of culprit lesion in patients with non ST-segment elevation acute coronary syndrome. (14th October 2021) - Chiarello, G; Guaricci, A I; Gherbesi, E; Pontone, G; Siena, P; Soldato, N
Abstract:  : INTRODUCTION An early evaluation of patients with non-ST elevation acute coronary syndrome patients (NSTE-ACS) is important to choose the appropriate treatment strategy. In this setting of patients, conventional echocardiographic assessment may reveal normal myocardial kinesis in 25 to 76% of cases. Global and territorial longitudinal strain (GLS and TLS, respectively) may be an early and accurate non-invasive tool for prediction of multivessel CAD in patients with NSTE-ACS. AIM To evaluate the ability of TLS to predict culprit lesions in patients with NSTE-ACS. Material and method: We studied 183 patients diagnosed with NSTE-ACS, in our Institution over 2 years of time. Conventional echocardiography and 2D speckle tracking echocardiography (STE) imaging were performed by two experienced echocardiographers, who were blinded to patient characteristics. The TLS was identified as the mean value of the segments'strain as respect to each vessel territory.Coronary angiography was performed in all patients. Significant CAD (luminal stenosis more than 70% in a major epicardial coronary vessel) and culprit lesion were identified and threated by PTCA when appropriate. Results: A significant difference between mono- and tri-vessel CAD in the variation of WMSI has been demonstrated. There was a statistically significant difference between both 3-vessels vs 1-vessel disease and 2-vessels vs 1-vessel disease in changing of TLS-LAD, TLS-RCA and TLS-Cx values (p-value <0.001). There was a significant difference between 3-vessels vs 2-vessels disease for TLS-RCA values. There was a statistically significant difference for WMSI-LAD, WMSI-CX and WMSI-RCA values whether the respective artery was involved or not. Variations of TLS were statistically significant both when the territorial tributary artery was involved and also if the artery represented the culprit lesion (p-value TLS-LAD <0.001, TLS-LAD culprit <0.001, TLS-CX<0.001, TLS-cx culprit <0.001, TLS-RCA <0.001, p-value TLS-RCA culprit 0.022). A regression model was performed comparing the variation of WMSI as respect to the variation of WMSI+TLS in the territory of culprit lesions. For WMSI- LAD the OR was 0.94 and for TLS-LAD the OR was 1.19 and the p-value of the addition was 0.001. The OR of WMSI-CX was 1.76 and for TLS-CX the OR was 1.40 and the p- value of the addition was 0.001. The OR of WMSI- RCA was 0.71 and for TLS- RCA the OR was 1.17, the p- value of the addition was 0.019. Conclusion: TLS allows an accurate identification of the culprit lesion in patients presenting with NSTE-ACS. TLS can be considered as part of routine echocardiography on top of WMSI in early evaluation for a better clinical assessment in this subset of patients. Funding Acknowledgement: Type of funding sources: Public hospital(s). Main funding source(s): Policlinico di Bari